2020
DOI: 10.3390/ijms21030823
|View full text |Cite
|
Sign up to set email alerts
|

Myoblast Migration and Directional Persistence Affected by Syndecan-4-Mediated Tiam-1 Expression and Distribution

Abstract: Skeletal muscle is constantly renewed in response to injury, exercise, or muscle diseases. Muscle stem cells, also known as satellite cells, are stimulated by local damage to proliferate extensively and form myoblasts that then migrate, differentiate, and fuse to form muscle fibers. The transmembrane heparan sulfate proteoglycan syndecan-4 plays multiple roles in signal transduction processes, such as regulating the activity of the small GTPase Rac1 (Ras-related C3 botulinum toxin substrate 1) by binding and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 35 publications
4
18
0
Order By: Relevance
“…Although syndecan-4 knockout mice cannot regenerate damaged muscle tissue (Cornelison et al, 2004), the details of the underlying mechanism remain unknown. Previously, we reported that syndecan-4 affects myoblast proliferation by modulating myostatin signaling and the G1/S transition in cell cycle (Keller-Pinter et al, 2018), and directional persistence of random cell migration is affected by syndecan-4-mediated Tiam-1 expression and distribution (Becsky et al, 2020). In this study, we demonstrated that syndecan-4 knockdown induced nanoscale alterations in the lamellipodial actin fiber structure of migrating myoblasts.…”
Section: Introductionsupporting
confidence: 56%
See 2 more Smart Citations
“…Although syndecan-4 knockout mice cannot regenerate damaged muscle tissue (Cornelison et al, 2004), the details of the underlying mechanism remain unknown. Previously, we reported that syndecan-4 affects myoblast proliferation by modulating myostatin signaling and the G1/S transition in cell cycle (Keller-Pinter et al, 2018), and directional persistence of random cell migration is affected by syndecan-4-mediated Tiam-1 expression and distribution (Becsky et al, 2020). In this study, we demonstrated that syndecan-4 knockdown induced nanoscale alterations in the lamellipodial actin fiber structure of migrating myoblasts.…”
Section: Introductionsupporting
confidence: 56%
“…Here we show the effect of syndecan-4 silencing on Ca 2+ distribution, centrosome positioning, and actin nanostructure after 8 h directional migration following wound scratching. Interestingly, the average speed values of the migrating C2C12 cells were similar in the case of both random (Becsky et al, 2020) and directional migration.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In the process of long-distance extension of cells, it is necessary to protrude a wide and flat flaky prosthetic foot on the cell surface, and Rac1 is needed to form this structure (21,22). The finger-like structures formed in lamellipodium is called filopodia, which is regulated by Cdc42 and participates in cell adhesion (23). Due to different environments, migrating cells present morphological differences (such as expansion, contraction and polarization), which are controlled by the activity levels of cytoskeleton regulatory protein Rho-GTPase (24).…”
Section: Rac1 Regulates Cell Adhesion Morphology and Movementmentioning
confidence: 99%
“…Skeletal muscle is a dynamic tissue with the ability to regenerate successfully following injury and to adapt in response to growth or exercise. Skeletal muscle stem cells, also named satellite cells, are the main drivers of the plasticity, maintenance, and regeneration of skeletal muscle [ 1 , 2 , 3 ]. Under resting conditions, these cells are mitotically and physiologically quiescent, but in response to increased physiological muscle loading or injury, they are activated and re-enter the cell cycle to generate satellite cell-derived myoblasts.…”
Section: Introductionmentioning
confidence: 99%